2014
DOI: 10.1159/000356191
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Antidepressants on Overall Well-Being and Self-Reported Depression Symptom Severity in Youth: A Meta-Analysis

Abstract: Background: Recent meta-analyses of the efficacy of second-generation antidepressants for youth have concluded that such drugs possess a statistically significant advantage over placebo in terms of clinician-rated depressive symptoms. However, no meta-analysis has included measures of quality of life, global mental health, self-esteem, or autonomy. Further, prior meta-analyses have not included self-reports of depressive symptoms. Methods: Studies were selected through searching Medline, PsycINFO, and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…A meta-analysis examining adjunctive atypical antipsychotic treatment for depression, for instance, showed that while observer ratings of depression decreased with pharmacotherapy use, there was little evidence of improvement in patients’ QOL (Spielmans, Berman, Linardatos, Rosenlicht, Perry, & Tsai, 2013). Additionally, a meta-analysis investigating the efficacy of antidepressants for depressed youths demonstrated that despite improvement in clinician-rated depression symptoms following the use of antidepressants, patients did not exhibit improvement in overall well-being and QOL (Spielmans & Gerwig, 2014). …”
mentioning
confidence: 99%
“…A meta-analysis examining adjunctive atypical antipsychotic treatment for depression, for instance, showed that while observer ratings of depression decreased with pharmacotherapy use, there was little evidence of improvement in patients’ QOL (Spielmans, Berman, Linardatos, Rosenlicht, Perry, & Tsai, 2013). Additionally, a meta-analysis investigating the efficacy of antidepressants for depressed youths demonstrated that despite improvement in clinician-rated depression symptoms following the use of antidepressants, patients did not exhibit improvement in overall well-being and QOL (Spielmans & Gerwig, 2014). …”
mentioning
confidence: 99%
“…When all trials are combined, mean weighted improvement on the HRSD was 8.3 points for fluoxetine and 7.3 points for placebo. Indeed, the FDA has approved antidepressants that demonstrated no advantage over placebo on such measures (Spielmans & Gerwig, 2014). 1 Eli Lilly's application to the FDA for the approval of fluoxetine in children with major depression included results from two acute efficacy trials.…”
mentioning
confidence: 99%
“…• The most powerful evidence of efficacy for antidepressants over placebo in depressed youth is on clinician-rated depression measures, where their benefit is d = .20, literally the smallest of small effects according to Cohen's convention (92). • On self-reports of depressive symptoms, or across measures of quality of life, global mental health, or autonomy, antidepressants have failed to beat placebo (77). • The drug industry has under-reported antidepressant-related harms, including of suicidality (54,55,57).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it seems that clinicians responded to the warning in a reasonable fashion. In viewing antidepressants as increasingly risky due to the warning, they prescribed them less often to the people who had the least need for them while still maintaining the same level of treatment with the most impaired depressed youth, albeit with likely quite limited efficacy based on RCT findings (76,77). The subsequent return to prewarning rates of antidepressant use in the later postwarning years suggests that the Black Box warning's impact did not last, contrary to claims made by several researchers who have suggested that the warning has led to decreased antidepressant prescription rates.…”
Section: Longer-term Trends After Regulatory Warningsmentioning
confidence: 99%